A New Approach towards Ideal Location Selection for PV Power Plant in India - Suprava Chakraborty; Pradip Kumar Sadhu; Nitai Pal (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
India is the seventh largest country in the world, blessed with adequate solar radiation, therefore to setting up a Photovoltaic power plant is a lucrative option. In actual field conditions the performance of the PV modules vary significantly from its Standard Test Condition (STC) due to large change in environmental conditions. It is very important to study the exact meteorological parameters for different locations in India before installation of a Photovoltaic power plant. In this paper, the long-term meteorological parameters for the seventy considered locations in India from National Aeronautics and Space Administration (NASA) renewable energy resource website (Surface Meteorology and Solar Energy) are collected and analyzed in order to select an ideal location for installation of PV power plant. This paper helps the investors, Ministry of New and Renewable Energy (MNRE), Electricity Authority and Planning Commission to select proper locations for installation of PV power plant.